PERANCANGAN SISTEM INFORMASI PENJUALAN HANDPHONE ONLINE BERBASIS WEB DI TOKO 321 CELL - Rustam, Rustam; Evalani, Rinda (LPPM Institut Teknologi Bisnis Dan Bahasa Dian Cipta Cendikia, 2023)
Currently, the 321 Cell Store sells conventionally, where consumers directly visit the store to make purchases. And the way to promote products is through brochures. The problem faced is that consumers do not know clearly the specifications of the products offered such as types of goods, pictures, product price information, product availability and descriptions, large costs for brochure printing and the speed of delivering information to potential customers. To see information about the products needed, consumers must come to the store or via telephone to find out detailed information. This causes a lot of wasted time that consumers need to obtain information. The sales information system to be built is web-based, using the PHP programming language and MySQL database. The system development method used in building a sales information system is the Extreme Programming model. Using the system design tool Use Case models, Activity Diagrams, Sequence Diagrams, and Class Diagrams. The result of this research is to produce an application of information system for selling cellphones at 321 Cell Kotabumi Store which can make it easier for customers to place orders and purchase cellphone products online via the web, anytime and anywhere as long as they are connected to the internet. This system produces information in the form of the types of mobile phone products offered such as models, prices, and specifications of mobile phones. This system can help the 321 Cell Store manage and monitor the results of orders or cellphone sales through sales reports on the web admin page.